Riots, pogroms, jihad: religious violence in Indonesia - Sidel, John Thayer (Cornell Univ. Press, 2006)
Indonesia : from ethnic conflict to Islamic terrorism? -- Situating "Islam" in Indonesia : the matrix of class relations -- Social transformation, 1965-1998 : konglomerat, kelas bawah, Islam -- Buildings on fire : church burning, riots, and election violence, 1995-1997 -- Crisis, conspiracy, conflagration : Jakarta, 1998 -- From lynchings to communal violence : pogroms, 1998-2001 -- Jihad and religious violence in Indonesia, 1995-2005